Reactive wafer bonding with nanoscale Ag/Cu multilayers. (15th July 2020) - Liu, Yu-chen; Lin, Shih-kang; Zhang, Hao; Nagao, Shijo; Chen, Chuantong; Suganuma, Katsuaki
Abstract: Reactive bonding using nanoscale multilayers based on the high specific surface/interface energy is a promising low-temperature and low-pressure wafer-bonding process. Herein, Si wafers were bonded using nanoscale Ag/Cu multilayers in N2 or the ambient atmosphere. A flawless joint composed of Ag-rich and Cu-rich face-centered cubic (fcc) phases was achieved in N2 with 22.2 MPa shear strength. However, a peculiar "fcc-(Ag)+voids/Cu2 O/fcc-(Ag)+voids" three-layer sandwich structure with 11.1 MPa shear strength was formed due to significant out segregation of Cu toward the bonding-interface in the ambient atmosphere. The bonding mechanism and the role of oxygen were unveiled based on CALPHAD (CALculation-of-PHAse-Diagram) thermodynamic modeling. Graphical abstract: Image, graphical abstract